Statistics on Small Networks in Construction Design Offices - Jaramillo, Kleber; Castillo, Tito; Zarate, Andrea; Andrade, Alexis; Herrera, Rodrigo (Civil Engineering Journal, 2025)
This study explores communication structures in construction design offices using social network analysis (SNA) to compare directed and undirected networks. The objective is to understand how these network types influence hierarchy, information flow, and collaboration within small design teams. Data were collected from nine construction design offices, constructing both directed and undirected networks based on survey responses. Various graph theory metrics, including clustering coefficient, network diameter, centrality, and connectivity, were analyzed to assess communication efficiency. The results show that directed networks emphasize hierarchical structures with limited reciprocal exchanges, while undirected networks confirm mutual interactions, fostering collaboration. Despite variations in size, most networks exhibit small-world properties, indicating that key individuals act as bridges, ensuring effective communication. These findings highlight that network structure, rather than size, plays a crucial role in team coordination. This study contributes to Architecture, Engineering, and Construction (AEC) research by providing insights into optimizing team dynamics, balancing hierarchical control with flexible collaboration, and improving project management strategies. Doi: 10.28991/CEJ-2025-011-03-02 Full Text: PDF